Contribution of zooplankton nutrient recycling and effects on phytoplankton size structure in a hypereutrophic reservoir. (12th September 2022) - Butts, Tyler J; Moody, Eric K; Wilkinson, Grace M
Abstract: Consumer nutrient recycling influences aquatic ecosystem functioning by altering the movement and transformation of nutrients. In hypereutrophic reservoirs, zooplankton nutrient recycling has been considered negligible due to high concentrations of available nutrients. A comparative analysis ( Moody and Wilkinson, 2019 ) found that zooplankton communities in hypereutrophic lakes are dominated by nitrogen (N)-rich species, which the authors hypothesized would increase phosphorus (P) availability through excretion. However, zooplankton nutrient recycling likely varies over the course of a growing season due to changes in biomass, community composition and grazing pressure on phytoplankton. We quantified zooplankton, phytoplankton and nutrient concentration dynamics during the summer of 2019 in a temperate, hypereutrophic reservoir. We found that the estimated contribution of zooplankton excretion to the dissolved nutrient pool on a given day was equivalent to a substantial proportion (21–39%) of the dissolved inorganic P standing stock in early summer when P concentrations were low and limiting phytoplankton growth. Further, we found evidence that zooplankton affected phytoplankton size distributions through selective grazing of smaller phytoplankton cells likely affecting nutrient uptake and storage by phytoplankton. Overall, our results demonstrate zooplankton excretion in hypereutrophic reservoirs likely helped drive springtime phytoplankton dynamics through nutrient recycling while grazing influenced phytoplankton size distributions.